MARKETING STRATEGIES AND MODELS OF KAMPUNG CHICKEN PRODUCTS BY WOMEN FARMING GROUP (KWT) IN MALANG DISTRICT: IMPROVING WOMEN'S ACCESS AS ONLINE MARKET PLAYERS (International Conference on Social and Islamic Studies, 2021)
Marketing of Kampung Chicken products in the form of carcasses and processing can now be done through the online market. Analysis of marketing strategies and models is needed so that the Women Farmers Group (KWT) can access the online market and become marketers of kampung chicken carcasses. This study aims to determine the chosen marketing strategy and model for KWT in increasing KWT's access to the online market. This study uses a descriptive method, while the approach method is a case study technique. The population and sample of this research are members of KWT Arjuno Lawang and KWT Mawar Singosari Malang Regency. Determination of the sample using purposive sampling and snowball sampling, with specific considerations set 65 people as informants. Analysis of the selection and setting of strategic priorities using EFE and IFE Matrix, SPACE Matrix, SWOT Matrix, SWOT Strategy Combination Planning Matrix, and QSPM Matrix. Meanwhile, the analysis of the model design planning or marketing channel pattern is carried out by discussion, namely Focus Group Discussion (FDG). The results of the analysis of the SWOT strategy (Score: 3.45) and QSPM (Score: 4.45) that the strategy of the Women Farmers Group (KWT) Arjuno Lawang and the Women Farmers Group (KWT) Mawar Singosari in marketing chicken carcass products and processing kampung chicken is a strategy development of business prospects utilizing WhatsApp (WA) social media. Through the FGD, a model or pattern of distribution of orders for chicken carcass products and processing of kampung chicken was produced by KWT members through two channels, namely directly to final consumers (households) and food stalls that have become KWT customers.